Environmental chemistry and toxicology of mercury - Cai, Yong, 1961-; Liu, Guangliang, 1972-; O'Driscoll, Nelson J., 1973- (Hoboken, N.J. : Wiley, 2012)
"This book provides the fundamentals, recent developments, and future research needs for critical mercury transformation and transport processes, as well as the experimental methods that have been employed in recent studies. The coverage discusses the environmental behavior and toxicological effects of mercury on organisms, including humans, and provides case studies at the end of each chapter. Bringing together information normally spread across several books, this text is unique in covering the entire mercury cycle and providing a baseline for what is known and what uncertainties remain in respect to mercury cycling"--
Includes bibliographical references and index.
Keywords: Mercury -- Environmental aspects; Mercury -- Metabolism; Mercury -- Toxicology